Pengaruh Kualitas Pelayanan Terhadap Consumer Satisfaction Dimediasi Minat Pembelian - Husna, Murni; Mala, Iva Khoiril; Sutantri, Sutantri (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2023)
The research aims to find out the influence of service quality on customer satisfaction and purchase interest in the case study of Pak No meatball stall. This research was conducted on all customers who bought meatballs at that place. With a population of 100 people and a sample of 78 people. In taking samples, researchers used purposive sampling techniques. The data analysis technique uses Simple Linear Regression analysis using the SPSS 29.01 for Windows application. Based on the results of this research data analysis, it is known that service quality influences customer satisfaction or customer comfort. This can be seen from the significance value of 0.001 < 0.05.